Discussing depression disorder in older adult and elderly - Lee, Sim Chuan; Wong, Yik Wah; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni (AENSI Publisher, 2015)
Depression has become a common cause of death which bears the risk similar to the smokers. It has reported in United Kingdom that suicide has become the most common death of those whose age below 35, and additionally, World Health Organization data has statistically shown that the proportion of suicide rate of a late life depression has become the highest among any other age group. On the other hand, the overall population is aging faster than before due to longer lifespan, lower mortality rate, lower birth rate etc. The group of the older adult and elderly has become an issue of the society. Therefore, it is very important for us to see what is happening to the older adult and elderly, and understand what it is about late life depression. Hence, from the research we have done upon the sources we’ve got from the internet, we restatement the theory of how depression are start, how do we deal with it, and what do we get from it. Depression in older adult and elderly can be caused by personal life event, physical or mentally changes due to aging, and the treatment for the patient of older adult is similar to the younger patients, it is differ from the condition of the patient. This writing is to discuss the research on the depression among the group of age 50 and above, to study the details of why and how’s the life of them who needed extra cares and concern, to acknowledge the issue of late life depression among the society, and to point out a series of theory that were stated by the past research we can get from different sources. This paper contains the critical analysis of depression disorder in older adult and elderly. It covers the introduction of depression in elderly, definition, and the background information of depression, causes of depression and the treatment of depression. After a deep analysis of this topic, readers are expected to know the knowledge of depression and depression types and also the root of it causes.